FEATURES OF REARFOOT INJURIES IN PATIENTS WITH MULTISYSTEM TRAUMA - V. B. Bondarev; V. O. Kalensky; P. A. Ivanov (Неотложная медицинская помощь, 2016)
Background. Rearfoot injuries occur 2.5 times more often in a multisystem trauma than in patients with an isolated injury. The foot trauma is often misdiagnosed at the stage of intensive care treatment. Up to 22% of victims with foot injuries become disabled.Aim of the study. The aim of the study is to determine distinctive characteristics of rearfoot injuries in patients with multisystem trauma.Material and methods. We peformed a retrospective study of 89 cases of rearfoot injuries in patients admitted to the N.V. Sklifosovsky Research Institute for Emergency Medicine in 2011–2013.Results. There were 128 calcaneus and talus fractures. Middle-aged male patients (39±14.5 years) prevailed.Conclusion. We found several peculiarities: the common mechanism of an injury was the fall from a height (64%). Up to 40% of patients with multisystem trauma had injuries of two and more anatomic areas. The multisystem spinal (lower thoracic and lumbar) injury was detected in 29% of patients. In 38% of cases we revealed polysegmental fractures of lower limbs. In patients with polytrauma, multiple foot injuries were diagnosed in 31 cases (35%), most common were bilateral calcaneus fractures. We also diagnosed 60% of Gustilo and Anderson open fractures of III type.